GWARANCJA PRZY SPRZEDAŻY KONSUMENCKIEJ (WYBRANE ZAGADNIENIA) - Król, Adrian (Zeszyty Prawnicze, 2017)
Consumer’s Guarantee (Selected Issues) Summary The hereby article is truly devoted to the important issues related to the guarantee related to the purchase. The contract of sale is the most often concluded contract within consumer’s trade, and thus it is difficult to reprice its practical importance both in economical and legal terms. One can even say there has recently been recast of one law contracts in its detailed part, from sale contract into the vast and complex law of sale. Today more and more, its subject are goods of a high market value, which are under guarantee of quality – either given by the manufacturers or seller. However, whether under what conditions, or if in general the guarantee will be granted, decides mainly the guarantor. Therefore quite often the consumer has little influence on the contest of the guarantee. All above gives precise analysis of the complex institution. The hereby paper the author presents a detailed guarantee, discussing in particular such issues as the role and nature of legal guarantees, the person responsible for the guarantee, the powers given to the customer , the significance of the document. The author recalls at the same time the views of the doctrine of civil law as well as the jurisprudence in this area.